EFFECT OF PAPER SURFACE PROPERTIES ON INK COLOR CHANGE, PRINT GLOSS AND LIGHT FASTNESS RESISTANCE - (:unkn) unknown (EDITURA ACAD ROMANE, 2021)
Printability is a combination of paper-related factors that contribute to achieving the desired print quality level and relates to the paper's ability to absorb ink. An important property of ink on paper is its setting behavior. The spread and placement of the ink on the paper surface is affected by the surface structure of the paper. The surface topography of the paper is decisive in the process of ink placement on the paper surface. In this study, the effects of surface roughness of the paper on wettability, print gloss, ink color change and light fastness change were investigated. For this purpose, prints on papers with different surface roughness were made in accordance with ISO 12647-2 with Cyan color ink in accordance with DIN ISO 2846-1. The CIE L*a*b* and gloss values of the test prints, which were allowed to dry in order to detect color and print gloss differences on the paper surfaces, were measured periodically until the ink film was completely dry. In addition, the effects of the paper surface on the light fastness of the ink were measured and recorded. The results were discussed in terms of print quality.
Keywords: paper; surface roughness; contact angle; surface energy; printability; QUALITY; PRINTABILITY; WATER